The Influence Of Product Quality, Brand Trust, And Customer Satisfaction On Customer Loyalty Of Bening’s Skincare Products In Batam - Aurora Maulidina Nabila; Triana Ananda Rustam (LPPM Universitas Buddhi Dharma, 2024)
The evolution of time and technology has ushered in a new era where societal needs have expanded beyond the basics of sustenance to include elements like appearance and beauty. This shift has catalyzed significant growth within the beauty industry, with services proliferating to meet the burgeoning demand. Understanding the dynamics that govern customer loyalty in this context is crucial for businesses operating within the sector. This study aims to explore how product quality, brand trust, and customer satisfaction impact the loyalty of customers using Bening's Skincare products in Batam. A sample size of 100 respondents was selected through purposive sampling, a method aimed at ensuring representation by deliberately selecting participants based on specific criteria. Data was collected through questionnaire distribution to gather valuable insights from the study population. The analysis utilized SPSS application version 25, involving data quality tests, classical assumption tests, influence tests, and hypothesis testing, with multiple linear regression as the analysis method. Results indicated that Product Quality, Brand Trust, and Customer Satisfaction had a positive and significant impact, either individually or collectively, on Customer Loyalty towards Bening's Skincare products in Batam.